The Digital Legal Landscape: Unveiling Institutional Contributions, Research Focus, and Influential Authors - Wicaksono, Ageng; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This data article delves into the intersection of cyberlaw and focus groups, sourcing data from Scholarly Works on lens.org via keywords "cyberlaw or cyber law and focus group," filtered for law-related journal articles. The study uncovers institutional contributions, active years in article production, key study areas, and prolific authors. It highlights the proactive role of institutions like the University of South Africa and Singapore Management University, emphasizing cyberlaw's significance in addressing digital challenges. The focus on legal aspects related to cybercrime and internet security emerges as critical. These insights are invaluable, guiding future research in comprehending the legal dynamics of the digital world and its implications. Highlights: Institutional Contributions: Highlights proactive roles of specific institutions in cyberlaw research. Critical Study Areas: Emphasizes legal aspects of cybercrime and internet security. Guiding Future Research: Provides essential insights for understanding digital legal dynamics and implications. Keywords: Institutional Contributions, Cybercrime, Internet Security, Cyber Law, Focus Groups